Piet de Rooy, A Tiny Spot on the Earth: The Political Culture of the Netherlands in the Nineteenth and Twentieth Century - Moore, Bob (BMGN - Low Countries Historical Review, 2016)
Piet de Rooy, A Tiny Spot on the Earth: The Political Culture of the Netherlands in the Nineteenth and Twentieth Century (Amsterdam: Amsterdam University Press, 2015, 405 pp., ISBN 978 90 8964 704 7).